PENGARUH GAYA KEPEMIMPINAN, BUDAYA ORGANISASI, DAN PENGEMBANGAN KARIR PADA KOMITMEN ORGANISASI DAN KINERJA - Sosiawan Ma’mun (EKUITAS (Jurnal Ekonomi dan Keuangan), 2013)
The research aim to analysis the affects of: (1) the leadership style; (2) the organization culture; (3) the carrier development toward organization commitment and (4) the leadership style; (5) the organization culture; (6) the carrier development; (7) the organization commitment toward performance. This research applied on Regional Government Makassar City. Population all of medic employees as amount 590 persons. Sample as amount 382 respondents  with analysis used Structural Equation Model with aim AMOS 18 program.The result of research found that the leadership style have positive affect and insignificant toward commitment. This mean that the application of leadership style such as forced, autocracy, affiliation, quickly, democracy and trainer cannot do implementation of work totality by employee in commitment to progress the organization. The leadership style have ngative and significant affect toward performance through commitment. This show the application of leadership style not yetable to increase the performance, because the employee have low commitment. The carrier development give dominant, positive and significant affected toward organization commitment, which mean that the employee very desire, opportunity to increase the job carrier, so get affected of work commitment.